Investor Attention, Market Liquidity and Stock Return: A New Perspective - Wang, Bin; Long, Wen; Wei, Xianhua (Asian Economic and Financial Review, 2018)
We propose a new method to measure the investor attention paid to a specific industry using search data from search engine. Instead of taking company names or stock codes as keywords, we select keywords from a corpus of texts concerning a given industry by text-analysis technique such as TextRank algorithm. Two indices were constructed by principal component analysis method, including a positive index and a negative index. The empirical analysis demonstrates that the influence of investor attention on market liquidity is coincident and significant, and the effect on industry stock index return is less significant.